A molecular dynamics study of silicene reinforced cement composite at different humidity: Surface structure, bonding, and mechanical properties. (12th July 2021) - Hou, Dongshuai; Zhang, Wei; Chen, Zheng; Zheng, Qi; Sun, Guoxing; Liang, Rui
Highlights: The silicene can enhance the strength and stability of C–S–H interlayer region. This silicene significantly improves the strength and plasticity of C–S–H. The water molecules would weaken the stability of C–S–H interlayer region. C–S–H/silicene breaks in the internal area rather than interlayers in a dry state. Abstract: As the silicon counterpart of graphene, silicene has a great potential in reinforcing cement-based materials due to its outstanding physical properties. In this paper, the surface structure, bonding, mechanical performance and failure mechanism of silicene reinforced calcium-silicate-hydrate composite (C-S-H/silicene) with different humidity were investigated by molecular dynamics simulations. It has been demonstrated that the incorporation of silicene nanosheet can effectively bridge the upper and lower layers of C-S-H and enhance the strength and stability of the interlayer region of C-S-H via various chemical bonds (e.g. Si-Os-Si covalent bonds). This bridging effect provided by silicene nanosheet significantly improves the strength and plasticity of C-S-H. However, the penetration of water molecules may weaken the stability of these chemical bonds, leading to the degradation of tensile strength. Besides, C-S-H/silicene breaks in the internal area rather than interlayers in a dry state during the failure process. This can be explained that Si-Os-Si bonds are strong enough to connect the silicene sheet and C-S-H layers and hinder the propagation of cracks. Hopefully, the reinforce mechanism of silicene on C-S-H could provide new insights on understanding and predicting performance of silicene under specific conditions.